Characterisation of the Chimeric Proteins of Vp3 from Chicken Anemia Virus with Nucleoprotein from the Newcastle Disease Virus - Othman, Zulkefley (2006)
Chicken anemia virus (CAV) causes aplastic anemia, generalized lymphoid atrophy and increased mortality in susceptible chickens.Infections with CAV are considered to be economically significant because of the clinical disease associated with vertical transmission and its potential for inducing immune dysfunction alone or in combination with other pathogens.CAV infection can be detected using several serological methods such as serum neutralization, immunofluorescence assay and enzyme-linked immunosorbent assay (ELISA).With small size and abundant amount in infected cells, VP3 protein of CAV is a good choice for virus detection. Due to its poor solubility,VP3 was unsuitable for immunogenicity studies. This protein was fused to the nucleoprotein (NP) of Newcastle disease virus (NDV),which has the ability to increase its solubility. The VP3 was expressed together with the NP protein in pTrcHis2 vector as full length (pTrcHis2NP+VP3FL) and truncated (pTrcHis2NP+VP3F1, pTrcHis2NP+VP3F2 and pTrcHis2NP+VP3F3). The chimeric protein of NP and full length VP3 reacted specifically with VP3 monoclonal antibody but not chimeric proteins containing truncated VP3.On the other hand, fusion of NP significantly improved the solubility of truncated but not the full length VP3 protein.The estimated solubility of NP with full-length VP3 and truncated VP3 proteins was 15 and 50 %,respectively.In order to determine the immunogenicity of the expressed VP3 proteins, protein lysates of chimeric protein of NP with full length VP3 was injected into specific-pathogen-free (SPF) chickens and the sera was collected. However, the sera failed to react with whole CAV and VP3 protein when tested using ELISA or Western blot.The sera showed positive reaction with Western blot analysis against purified NP and NDV suggesting that the NP, but not the VP3 protein,was immunogenic and able to induce antibody responses.The inability of the SPF chickens to induce VP3-specific antibody responses was probably due to the small size of VP3 and the low solubility of the protein.In addition,the VP3 protein is relatively unstable based on analysis using ProtParam program.The study also revealed that hydrophobicity graft of all the chimeric proteins were similar with the solubility analysis performed previously.Thus,the expressed chimeric protein of NP and VP3 is not suitable for use as an antigen in the production of antibody for the development of VP3 protein as diagnostic marker.More studies are required before the potential application of the VP3 in the diagnosis of CAV can be ascertained